Resilience and mental health: A longitudinal cohort study of Chinese adolescents before and during COVID-19 - Shi, Wei; Zhao, Li; Liu, Min; Hong, Binxue; Jiang, Lihua; Jia, Peng (Frontiers in Psychiatry, 2022)
Background The COVID-19 outbreak has resulted in mental health issues, mainly depression and anxiety, prompted by stressors such as the need to maintain social distance, adapting to quarantine, and lockdown policies. Resilience may be vital in protecting individuals from mental disorders. However, few studies have examined the longitudinal relationships between resilience and mental disorders (i.e., depression and anxiety) among adolescents before and during the COVID-19 pandemic. Objective This study aimed to examine the association between resilience, depression, and anxiety among Chinese adolescents before and during COVID-19 using a longitudinal cross-lagged model. Methods A total of 7,958 Chinese adolescents completed a baseline survey in the month before COVID-19 and were followed up after the COVID-19 lockdown. Structural equation modeling analyses were applied to evaluate the associations between resilience, depression, and anxiety after controlling for three covariates (i.e., gender, age, and COVID-19 effect). Results A higher level of resilience before COVID-19 significantly predicted decreased severity of depression and anxiety after the lockdown. Moreover, the mean level of resilience and prevalence of mental disorders (i.e., depression and anxiety) among Chinese adolescents decreased after the lockdown. These findings suggest resilience is a vital protective factor against depression and anxiety among adolescents. Furthermore, younger participants and those less affected by the pandemic could be more resilient. No significant link was found between gender and resilience in the second wave. Conclusions Resilience is an essential protective factor for reducing mental disorders among Chinese adolescents exposed to COVID-19. Resilience-related interventions should be developed to efficiently promote mental health recovery among youth during pandemics.